Kajian Fiqih Wanita Tentang Taharah Haid Pada Siswa Mi Al Ihsan Banyuwangi - Endhang Suhilmiati; Erisy Syawiril Ammah; Sudarsri Lestari (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this subserving is provide an introduction and understanding of menstruation period to students of MI Ihsan, especially who are already in high class (IV, V, & VI). After the socialization activities, it is hoped that they will no longer be confused about prohabition and imperative during menstruation, besides that, students are also expected to be able to do the correct menstrual period in accordance with Islamic law. Before doing socialization activities, the team conducted interviews and observations to determine the conditions in the field. Socialization activities are devided in 4 sesons, that is opening, giving material, question and answer, and closing.